Perceived Barriers to Antepartum HIV Medication Adherence in HIV Infected Pregnant Women - Leilah Zahedi-Spung; Marisa Young; Lisa B. Haddad; Martina L. Badell (Hindawi Limited, 2018)
Introduction. Although rare, perinatal HIV transmission still occurs in the United States and most transmissions are preventable. We aim to identify patient barriers to antiretroviral therapy (ART) adherence during pregnancy and assess patient understanding of perinatal transmission. Methods. This cross-sectional survey recruited HIV positive postpartum women at a large safety net hospital in Atlanta, Georgia, between January 2016 and February 2018. Survey questions included demographic characteristics, HIV history, knowledge of perinatal transmission, and ART adherence. Perinatal and HIV outcomes were assessed using chart abstraction. Results. Of the 70 HIV infected postpartum women delivered at a large safety net hospital in Atlanta, GA, 45 women were eligible and consented to participate. Participating women were aged 18 to 40 years with an average age of 29 years old, 93% of participants were African-American, and 68% had ≥3 pregnancies. The majority of participants (75%) reported daily ART adherence. "Forgetting" was the most frequent reason for missing pills (57%). Thirteen women had a detectable viral load at the time of delivery and nine of those women had a viral load greater than 1000 copies/mL. Approximately 85% of women who correctly stated ART medications decrease perinatal transmission risk reported daily adherence compared with 50% of women without that knowledge (OR 5.6, 95% CI 1.17, 26.7). Almost half of women (40%) either did not know or believed a vaginal delivery, regardless of viral load, would increase their risk of perinatal transmission. Conclusion. Overall, women who were diagnosed with HIV during the current pregnancy, those with planned pregnancies, and those who were on medications prior to pregnancy were more likely to report daily ART adherence. Detectable viral load at delivery is the greatest risk factor for perinatal transmission; therefore strategies to increase ART adherence are needed.